Perceived impacts of climate change and disaster risk management by rural communities in Ethiopia - Zerihun Yohannes Amare (Brawijaya University, 2018)
In developing countries including Ethiopia changing pattern of rainfall, increasing temperature, recurrent drought, massive land degradation, and poor performance of agricultural sector contribute for failure to meet the growing demands for food for the rural communities and left dependent on foreign food aid and seasonal migration. This study aims at examining the perceived impacts of climate change and disaster risk management by rural communities in Ethiopia. Cross-sectional socio-economic data were used. Dejen district was purposively selected as it is highly susceptible to climate related problems. Stratified and snowball sampling techniques were employed to select a sample of 398 households. Household survey was employed to collect data on climate change impacts perceived by local communities. Focus group discussions were carried out using guiding questions and seasonal calendar. Key informant interviews were used to triangulate households’ perceived climate change impacts. Field observations were used to observe biophysical, economic, social, and institutional features of the district. The results indicate that crop pests, soil erosion, crop disease, frost, drought, flood, hailstorm, and erratic rainfall were the major contributing factor for the loss of 50,555 quintals of agricultural cops over the period 2009-2016. The community seasonal calendar indicate that erratic rainfall, hailstorm, dry period, flood, landslide, livestock disease, crop disease and pests, and human diseases were the major climatic events in the study areas of rural communities. The lowland households were more susceptible to climate change impacts. Policy priority should be given based on the agro-ecology and households livelihood assets vulnerability levels